Taxonomic, nomenclatural and chorological notula of "Steerecleus" (Bryophyta: "Brachytheciaceae") in Uruguay - Fuertes, Esther; E. Marchessi, Jesús (Botanica Complutensis, 2013)
Steerecleus Robinson has been studied for Uruguay based on the specimens collected during the field expeditions on the Rio de la Plata’s estuary coast carried out in 2008. Two species have been recognised for the Uruguay bryophyte flora. Steerecleus serrulatus grows epiphyte in the evergreen forest of Eastern Uruguay (Department Rocha) and it is reported for the first time for the bryological flora of Uruguay. Descriptions and photographs are provided and the main differences among the taxa reported from Uruguay are discussed.